The gift relationship : from human blood to social policy - Titmuss, Richard Morris, 1907-1973 (Bristol, UK : Policy Press, 2018)
Richard Titmuss (1907-1973) was a pioneer in the field of social administration (now social policy). In 'The Gift Relationship', Titmuss compares blood donations in the US and UK, contrasting the British system of reliance on voluntary donors to the American one in which the blood supply is in the hands of for-profit enterprises. He concludes that a system based on altruism is both safer and more economically efficient.
Front Matter -- Contents -- Editorial Preface -- New Introduction -- List of tables -- Preface -- Introduction: human blood and social policy -- The transfusion of blood -- The demand for blood in England and Wales and the United States -- The supply of blood in England and Wales and the United States -- The gift -- The characteristics of blood donors in the United States -- The characteristics of blood donors in England and Wales -- Is the gift a good one? -- Blood and the law of the marketplace -- Blood donors in the Soviet Union and other countries -- A study of blood donor motivation in South Africa -- Economic man: social man -- Who is my stranger? -- The right to give -- Notes on blood and blood transfusion services in England and Wales -- Notes on the use of blood in the United States and England and Wales in 1956 -- Regional statistics for England and Wales, 1951-65 -- The Donor Survey: The characteristics of Donors -- Donor survey questionnaire -- Analysis of blood donor motives -- Acknowledgements -- Endnotes -- Bibliography -- Index
Includes new introduction.
Originally published in Great Britain in 1970 by George Allen and Unwin Ltd. Second edition published in 1997 by LSE Books. This edition [third edition?] published in 2018 by Polity Press.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, Oct. 26, 2018).
JSTOR
Keywords: Blood -- Transfusion -- Social aspects; Blood donors; Sang -- Transfusion -- Aspect social; MEDICAL -- Pharmacology; Blood donors; Blood -- Transfusion -- Social aspects